Life history of the ctenostome bryozoan Flustrellidra hispida in the White Sea - Kvach, A. Y.; Varfolomeeva, M. A.; Kotenko, O. N.; Sukhotin, A. A.; Kutiumov, V. A.; Grischenko, A. V.; Granovitch, A. I.; Ostrovsky, A. N. (Invertebrate Zoology, 2019)
The life history of the ctenostome bryozoan Flustrellidra hispida living intertidally on the brown alga Ascophyllum nodosum in the White Sea has been studied for the first time using colony mapping. Statistical analyses of colony composition (zooidal categories, states) encompassed budding, feeding, reproduction, polypide recycling and zooidal dormancy. This enabled documenting colony life and the overall population status at a much better resolution than using traditional methodology. In the ice-free period the colony composition correlated with colony size rather than time of season. F. hispida begins to breed much earlier in the year than all other bryozoan species whose life histories have been studied in the White Sea, and finishes last. Four colony generations co-exist. Young colonies appear in early spring (March) and reproduce in autumn (thus, yielding a daughter generation). Overwintered colonies of those two generations produce larvae whose settle- ment continues from spring to autumn (October) of the following year, with a break in August. This yields young colonies of daughter and granddaughter generations. Those granddaughter colonies that formed in spring breed in autumn (together with maternal colonies), thus adding a great-granddaughter generation. Maximal colony lifespan is about 2.5 years. Using published data, we compare the F. hispida life history traits in different geographical areas and discuss bryozoan life histories in the White Sea.